Witnessing beyond the Human : Addressing the Alterity of the Other in Post-coup Chile and Argentina - Jenckes, Kate, 1969- (Book collections on Project MUSE., 2017)
Provides an innovative and theoretically rigorous approach to the subject of testimony in Latin America. This book rethinks the nature of testimony beyond the ground of the human in works produced in Chile and Argentina from the 1970s to the present. Focusing on literature by Juan Gelman, Sergio Chejfec, and Roberto Bolaño, as well as art by Eugenio Dittborn, Kate Jenckes argues that these works represent life, death, and the relation between self and other "beyond the human," that is beyond the sense that we can know and represent ourselves and others, with powerful implications for our unders.